2009
DOI: 10.1080/03630260903039586
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Background and Radiation-Induced Apoptosis in Leukocytes of Individuals with α-Thalassemia Variants, Assessed by the Neutral Comet Assay

Abstract: To study effects of ionizing radiation on apoptosis induction in leukocytes of alpha-thalassemia (alpha-thal) variants compared to normal controls, venous blood samples were obtained from 10 healthy volunteers and 30 alpha-thal patients. Different types alpha-thal were diagnosed by multiplex polymerase chain reaction (PCR). Blood samples were irradiated with three Gy gamma rays, used for comet assay, immediately or 48 h after irradiation. Results show that the frequency of background as well as apoptosis in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The neutral comet assay was employed by Wilkins et al (19) to analyse radiation-induced apoptosis, and this approach was adopted by Omidkhoda et al (20) to look at the effect of superparamagnetic iron oxide on mesenchymal stem cells, and by Tarang et al (21) in a study of radiation-induced apoptosis in leucocytes from α-thalassemia patients. Russo et al (22), investigating the protective effects of a plant extract on human cells, simply regarded comets with a high tail moment (and high percentage tail DNA) as indicating apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The neutral comet assay was employed by Wilkins et al (19) to analyse radiation-induced apoptosis, and this approach was adopted by Omidkhoda et al (20) to look at the effect of superparamagnetic iron oxide on mesenchymal stem cells, and by Tarang et al (21) in a study of radiation-induced apoptosis in leucocytes from α-thalassemia patients. Russo et al (22), investigating the protective effects of a plant extract on human cells, simply regarded comets with a high tail moment (and high percentage tail DNA) as indicating apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…found that Ap % in irradiated groups immediately after irradiation were almost similar to those obtained from control samples. [ 24 ] Very low and dose-independent Ap 0Rad could be justified by the fact that apoptosis process might be initiated after irradiation, but it still has not been fulfilled to become morphologically detectable. [ 33 ] Hence, after irradiation, whole blood samples were incubated at 37°C in 5% CO 2 for 24 h to measure Ap 24Rad , as well.…”
Section: Discussionmentioning
confidence: 99%
“…This cytogenetic method has been widely used to measure IR-induced DNA damage and apoptosis in individual cells. [ 8 22 23 24 25 ]…”
Section: Introductionmentioning
confidence: 99%